2011
DOI: 10.1016/j.vetpar.2010.10.031
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic profile of Gallus gallus Linnaeus, 1758 experimentally infected by Plasmodium juxtanucleare Versiani & Gomes, 1941

Abstract: One of the species that causes avian malaria is Plasmodium juxtanucleare. It is commonly found in poultry, especially when the birds receive food free of coccidiostats. Since industrial and organic poultry breeding is increasing in the world and few studies have been conducted examining the clinical parameters of both healthy and infected birds, this work evaluated whether the infection caused by P. juxtanucleare in Gallus gallus provokes alterations in the birds' hepatic profile. We analyzed the activity of A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…It is important to note that in the present study, cardiomegaly and hepato-splenomegaly were observed among animals from the Malaria group. Spleen and liver enlargement were observed in earlier studies related to P. juxtanucleare infection in chickens (Vashist et al 2011). However, cardiomegaly and hydropericardium by P. juxtanucleare in experimentally infected SPF chicks are reported herein for the first time.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…It is important to note that in the present study, cardiomegaly and hepato-splenomegaly were observed among animals from the Malaria group. Spleen and liver enlargement were observed in earlier studies related to P. juxtanucleare infection in chickens (Vashist et al 2011). However, cardiomegaly and hydropericardium by P. juxtanucleare in experimentally infected SPF chicks are reported herein for the first time.…”
Section: Discussionsupporting
confidence: 57%
“…2009 a , b , Vashist et al . 2011). In those studies, it was also observed that P. juxtanucleare generally caused low parasitaemia and that parasitaemia is not always associated with anaemia or other changes.…”
Section: Discussionmentioning
confidence: 99%
“…compromises liver function. The high AST activity values in 66.6% of animals with avian malaria suggests the presence of liver injury, but further tests are needed for confirmation (Vashist et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…P. gallinaceum and P. juxtanucleare are two species that naturally infect domestic chickens, causing “chicken malaria” [ 129 ]. In one study, chickens infected with P. juxtanucleare were immunocompromised by intramuscular injection of methylprednisolone before receiving 50 mg/kg (body weight) Que or chloroquine diphosphate by gavage for four consecutive days [ 80 ]. Interestingly, both treated groups exhibited a significant decrease in parasitemia as compared to the control group ( p < 0.01) within the 30 days following the infection.…”
Section: Plasmodium Sppmentioning
confidence: 99%